Study on the existence of food born microflora and their drug resistant profile isolated from some fermented and non-fermented foods commonly available in Bangladesh - Jane, Tasnuva Nusrat; Tabassum, Nafisa; Acharjee, Mrityunjoy (Stamford Journal of Microbiology, 2019)
Present study depicted a complete microbiological profile of some popular fermented and non-fermented foods available in different food shops and restaurants in Dhaka city, Bangladesh. Furthermore, All the isolated strain were prepared to determine their survivability against some common synthetic drug through Kirby Bouer method. Total 60 samples of 20 categories (10 fermented and 10 non-fermented) unveiled the contaminating microbial flora up to 107 cfu/g including total viable bacteria and fungi in case of non-fermented food while the contamination rate was extremely low up to 105cfu/g in fermented food. Exploration of specific pathogenic bacteria was estimated such as E. coli, Salmonella spp, Vibrio spp., Staphylococcus spp. and Pseudomonas spp. within the range of 102 to 104cfu/g in non-fermented foods whereas only the Staphylococcus spp. was present in fermented food up to 103cfu/g. Among all the specific pathogens Salmonella spp., Vibrio spp. and Staphylococcus were significantly propagated in all categories of non-fermented samples up- to 104cfu/g. Total 17 available drugs were used against the identified bacterial strain. Most of the identified bacteria from fermented foods were found to be sensitive against commonly used antibiotics. Subsequently, five isolates from non-fermented foods were found to be 100% resistant against more than one antibiotic as multi drug resistant (MDR). Stamford Journal of Microbiology, Vol.8(1) 2018: 19-23